Pengaruh Efikasi Diri dan Perencanaan Karir Terhadap Kesiapan Kerja Siswa SMK - Annisa Nur Fitriyana, - (2021)
The purose of this study was determine and analyze the influence of self-efficacy and career maturity on student work readiness. This research uses explanatory survey research methods. This study used an explanatory survey research method with a quantitative approach. The data was collected by distributing self-efficacy questionnaires, career maturity questionnaires and work readiness questionnaires. The population in this study were students of class XI of state vocational school in Bogor city including SMK Taruna Terpadu 1, SMK Wiyata Mandala and SMK Al-Ghazaly which amounted to 242 students. While the sample in this study was taken as many as 150 students with proportional stratified random sampling techniques. The data analysis techniques used are descriptive analysis and path analysis. The results of this study indicate that 1) The general description of self-efficacy, career maturity and work readiness is in the medium category. 2) Self-efficacy has a positive and significant effect on career maturity as well as, 3) Self-efficacy and career maturity have a positive and significant effect on students' work readiness.